Parental rejection in childhood as a risk factor for intimate partner violence in adulthood - González Elices, Patricia; Vague Cardona, María Elvira (Psychology, Society & Education, 2023)
The aim of the study is to explore the relationship between the quality of the affective bonds of the father and mother in childhood with the violent manifestations and variables of psychological adjustment in adulthood of a group of men condemned by violence against women. The research was conducted on a sample of 107 men convicted of intimate partner violence referred by the Penitentiary Social Services to the intervention program with abusers “Context” of the University of Valencia. Participants were given different questionnaires (Parental Acceptance-Rejection Questionnaire, Alcohol Use Disorders Identification Test, Center for Epidemiologic Studies Depression Scale, Self-Esteem Scale, EI: Impulsivity Scale, State/Anger Expression Inventory Trait and State/Trait Anxiety Inventory) related to the variables associated with intimate partner violence, the results show the presence of two significant groups based on the acceptance and rejection perceived in childhood. Low self-esteem and high alcohol consumption were significant in relation to the perception of rejection in childhood. The results obtained have important implications when intervening with this type of population: the incorporation of psychoeducation programs for parents in order to prevent inappropriate behaviors in the adult population.